Encountering the Tsar : Nenets Epic Singing as a Representation of Historicity - Lukin, Karina (Suomen Antropologi: Journal of the Finnish Anthropological Society, 2023)
This article discusses Nenets epic songs, focusing on two texts collected at the beginning of the twentieth century in relation to the divergent historicities they represent. The process of gathering and publishing folklore is analysed as folklorisation, whereby the texts have come to represent a negation of the modern, but not giving voice to the singers or their communities. Nenets epic songs have served Finnish nationalism and Russian imperialism in creating hierarchies between Finns and their linguistic relatives and between different Russian ethnic groups, including Russians and the Nenets. The process of traditionalisation is discussed as a local strategy of recreating meaningful narration that relates both to tradition and other contextually relevant discourses. The songs discussed are shown to depict not specific past events, but rather Nenets historical experiences and understandings about their subaltern position and agency within the imperial context. Peer reviewed